Microbiota and Alcohol Use Disorder: Are Psychobiotics a Novel Therapeutic Strategy? - Rodriguez-Gonzalez, Alicia; Orio, Laura (Current Pharmaceutical Design, 2020)
In recent years, there has been an exciting focus of research attempting to understand neuropsychiatric disorders from a holistic perspective in order to determine the role of gut microbiota in the aetiology and pathogenesis of such disorders. Thus, the possible therapeutic benefits of targeting gut microbiota are being explored for conditions such as stress, depression or schizophrenia. Growing evidence indicates that there is bidirectional communication between gut microbiota and the brain that has an effect on normal CNS functioning and behavioural responses. Alcohol abuse damages the gastrointestinal tract, alters gut microbiota and induces neuroinflammation and cognitive decline. The relationship between alcohol abuse and hypothalamic-pituitary-adrenal axis activation, inflammation and immune regulation has been well documented. In this review, we explore the connection between microbiota, brain function and behaviour, as well as the mechanisms through which alcohol induces microbiota dysbiosis and intestinal barrier dysfunction. Finally, we propose the study of psychobiotics as a novel pharmaceutical strategy to treat alcohol use disorders.
Keywords: gut-brain axis